(untitled) (Innovative professional education, 2025)
The paper analyzes the role and importance of educational and practical centers for training qualified specialists capable of successfully addressing the main challenges of post-war reconstruction, ensuring the development of strategic sectors of the regional economy, which is the basis for a stable future of the country.